2009
DOI: 10.4321/s0213-61632009000100001
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of anxiety disorders in major depressive disorder: A clinical trial to evaluate neuropsychological deficit

Abstract: -Background and objectives:Various clinical aspects of Major Depressive Disorder (MDD) are related to the neuropsychological impairments characteristic of this illness. The aim of this study was to determine the relation between certain clinical variables of MDD -in particular the presence of comorbid anxiety disorders -and the neuropsychological performance of patients with MDD selected for a clinical trial.Methods: Using cluster analyses, we generated two groups of patients: one group with Major Depressive D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…Research suggests both that modern antidepressants do not have deleterious effects on cognitive test performance, and that that unmedicated patients may show more impaired attention functions compared to patients on medication (Den Hartog et al, 2003 ). Some studies also suggest that antidepressants may improve cognitive functions, including attention, in MDD patients (Fergusson et al, 2003 ), and that the effects of medication may be different on MDD from those with MDDA (Herrera-Guzmàn et al, 2009 ). Furthermore, functional imaging should be included to provide a greater understanding of the associated neurobiological correlates of cognitive control functions.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests both that modern antidepressants do not have deleterious effects on cognitive test performance, and that that unmedicated patients may show more impaired attention functions compared to patients on medication (Den Hartog et al, 2003 ). Some studies also suggest that antidepressants may improve cognitive functions, including attention, in MDD patients (Fergusson et al, 2003 ), and that the effects of medication may be different on MDD from those with MDDA (Herrera-Guzmàn et al, 2009 ). Furthermore, functional imaging should be included to provide a greater understanding of the associated neurobiological correlates of cognitive control functions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, they found that depressed patients without comorbid anxiety did not show impaired performance, thus pointing to a specific debilitating role of the comorbid anxiety in the impairment of attention control. However, other studies (e.g., Castaneda et al, 2010;Herrera-Guzmán et al, 2009) did not find any difference between depressed patients with and without comorbid anxiety disorders in tasks measuring attention or executive functions, challenging the claim that comorbid anxiety might damage attention control.…”
Section: Attentional Network In Co-occurring Generalized Anxiety Disorder and Major Depression Disorder: Towards A Staging Hypothesis Of mentioning
confidence: 88%
“…Nuestros resultados están en la línea de los de DeLucca et al (2005) quienes encontraron que los pacientes con TDM y trastornos de ansiedad comórbidos presentaban una mayor alteración de memoria que los pacientes con TDM sin ansiedad. No obstante debemos ser cautos al interpretar nuestros datos en esta dirección dado que otros trabajos han encontrado que la ansiedad comórbida con el TDM se relaciona con alteraciones de la atención y de las funciones ejecutivas (Basso et al, 2007 ) pero no de la memoria y otros trabajos no han encontrado relación entre la presencia de ansiedad comórbida con el TDM y disfunciones neuropsicológicas (Castaneda et al, 2010;Herrera-Guzmán et al, 2009). En nuestro trabajo observamos que un inicio del TDM a edades tempranas aumenta el riesgo de padecer alteraciones de la velocidad de procesamiento de la información y de generación de estrategias.…”
Section: Discussionunclassified
“…Otros trabajos sugieren que los pacientes que tienen TDM a una edad de inicio temprana presentan alteraciones neuropsicológicas más graves que aquellas personas que tienen un inicio del trastorno a una edad más tardía (Grant et al, 2001) y que un mayor número de episodios depresivos previos se relacionan con una presencia de alteraciones de memoria más graves (Gorwood, Corruble, Falissard y Godwin, 2008). Existen asimismo trabajos que encuentran que la comorbilidad del TDM con algún trastorno de ansiedad conlleva alteraciones neuropsicológicas más graves (DeLucca et al, 2005) mientras que otros trabajos que han explorado el mismo tópico sugieren que este fenómeno no se da (Castaneda et al, 2010;Herrera-Guzmán et al, 2009). El tratamiento con diferentes antidepresivos puede mejorar diversas funciones cognitivas de los pacientes deprimidos (Constant et al, 2005;Fergusson, Wesnes y Schwartz , 2003;Gallassi, Di Sarro, Morreale y Amore, 2006;Herrera-Guzmán et al, 2008;Herrera-Guzmán et al, 2010;Koetsier et al, 2002;Levkowitz, Catfori, Avital y Ritcher-Levin, 2002), pero esto es una fuente potencial de confusión para estudiar el perfil de alteraciones neuropsicológicas del TDM.…”
unclassified